THE EFFECT OF INTELLECTUAL CAPITAL AND CORPORATE SOCIAL RESPONSIBILITY (CSR) ON PROFITABILITY IN MINING COMPANIES LISTED ON THE IDX FOR THE 2021-2023 PERIOD - Istiqoma, Nurul; Frihatni, Andi Ayu (Institut Agama Islam Negeri Parepare, 2025)
Intellectual Capital emphasized that the company's resources are intangible assets, such as knowledge and skills that are very important to create added value and competitive advantage for the company in question. Corporate Social Responsibility (CSR) also emphasizes that companies must integrate social responsibility in their business strategies for long-term sustainability. This study aims to determine the influence of Intellectual Capital and Corporate Social Responsibility (CSR) on profitability in mining companies listed on the IDX. This study uses quantitative research. The population used is mining sector companies listed on the Indonesia Stock Exchange for the 2021-2023 period. The population used was 63 companies, the sample selection used the purposive sampling technique so that 12 companies were obtained. The methods used are classical assumption test, multiple linear regression and hypothesis test. The results of this study show that partially and simultaneously there is no significant influence between the variables of Intellectual Capital and Corporate Social Responsibility on the possibility. Although the company manages the resources it has to gain a competitive advantage to create company value, it has nothing to do with the profitability creation that is done. Corporate Social Responsibility if measured in a short-term horizon, such as annual, the positive impact is likely to not be detected quantitatively, so the results appear to be partially insignificant. Within the specific time period covered by this study, the impact on profitability may not have been realized or strong enough to show a significant simultaneous influence.